PENGUATAN KESEHATAN MENTALITAS KAUM TUNADAKSA MELALUI DESAIN RUANGAN - Atmaja, Filipus Jordan Kusuma; Santoso, J.M. Joko Priyono (Jurusan Arsitektur dan Perencanaan, 2024)
Society often looks down on people with disabilities, especially people with physical limitations. In Indonesia, especially in Jakarta, there are still many disabled people who have fragile mental problems due to accidents/hereditary factors, which cause them to be physically disabled. This causes a decline in the mentality of the disabled. In fact, the rights of persons with disabilities are regulated in Law Number 4 of 1997 which discusses Persons with Disabilities,